THE DEVELOPMENT OF THE APPLICATION OF A DATA WAREHOUSE AT PT JKL - Huda, Choirul; Sari, Rita Puspita; Haekal, Muharram Hasein; Agustaria, Tri (CommIT (Communication and Information Technology) Journal, 2012)
One rapidly evolving technology today is information technology, which can help decision-making in an organization or a company. The data warehouse is one form of information technology that supports those needs, as one of the right solutions for companies in decision-making. The objective of this research is the development of a data warehouse at PT JKL in order to support executives in analyzing the organization and support the decision-making process. Methodology of this research is conducting interview with related units, literature study and document examination. This research also used the Nine Step Methodology developed by Kimball to design the data warehouse. The results obtained is an application that can summarize the data warehouse, integrating and presenting historical data in multidimensional. The conclusion from this research is the data warehouse can help companies to analyze data in a flexible, fast, and effective data access.Keywords: Data Warehouse; Inventory; Contract Approval; Inventory; Dashboard